KAJIAN KONSERVASI LAHAN TERHADAP PENDAPATAN MASYARAKAT DALAM PENGELOLAAN SUMBERDAYA ALAM YANG BERKELANJUTAN - Drakel, Anhar (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2023)
Forest degradation has had an impact on environmental disasters such as: floods, landslides, water crises and global warming. Indonesia's deforestation rate from 2010 to 2021 was 1.6 million hectares per year. This figure increased to 2.84 million hectares per year from to 2022. The increasing rate of deforestation was influenced by forests not being managed properly, excessive logging and illegal logging, expansion of settlements and so on. This study examines forest resource management in the aspect of land resource conservation. The aim of this research is to find out the factors that influence society towards land conservation. The results of this study produced positive and negative impacts. The positive impact is increased income, while the negative impact can be seen as follows: reduced water, soil erosion, soil depletion, sedimentation, and depletion of biodiversity. The economic value of the losses is higher than the profits received. Quantitative results show that land conservation can have a direct influence on maintaining the stability of land resources.